Evaluating the effectiveness of public health interventions: the role and activities of the Cochrane Collaboration. Issue 4 (13th March 2006) - Waters, Elizabeth; Doyle, Jodie; Jackson, Nicki; Howes, Faline; Brunton, Ginny; Oakley, Ann
Abstract : Public health decision makers, funders, practitioners, and the public are increasingly interested in the evidence that underpins public health decision making. Decisions in public health cover a vast range of activities. With the ever increasing global volume of primary research, knowledge and changes in thinking and approaches, quality systematic reviews of all the available research that is relevant to a particular practice or policy decision are an efficient way to synthesise and utilise research efforts. The Cochrane Collaboration includes an organised entity that aims to increase the quality and quantity of public health systematic reviews, through a range of activities. This paper aims to provide a glossary of the terms and activities related to public health and the Cochrane Collaboration.